Strategi Digital Marketing Melalui Sosial Media Guna Meningkatkan Penjualan Produk - Sukoco, Sampir Andrean; Amanah, Khofiyah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Social media has become a marketing tool that is widely used in the digital era. This media has the advantage of being more effective and efficient. UD New Jaya Sakti is a business sector in the roof tile industry whose marketing also uses social media. The aim of this research is to find out how UD New Jaya Sakti implements social media marketing to increase its sales. The research method used is a qualitative method with a descriptive approach. Informants in this study were determined using purposive techniques. The research results show that UD New Jaya Sakti uses several social media to carry out its marketing, including using WhatsApp, Facebook and Instagram. Several social media features are used as a means for digital marketing. This marketing model was successful in increasing product sales. Keywords: Digital Marketing, Strategy, and Social Media